Vasculogenic Mimicry: Become an Endothelial Cell “But Not So Much” - Fernández-Cortés, Mónica; Delgado-Bellido, Daniel; Oliver, F. Javier (Frontiers in Oncology, 2019)
Blood vessels deliver oxygen and nutrients to every part of the body, remove waste and provide gateways for immune cells and other cells (pericytes, smooth muscle cells) that form part of these vessels around the principal endothelial cells. Vasculogenic mimicry (VM) is a tumor blood supply system that occurs independently of angiogenesis or endothelial cells, and is associated with poor survival in cancer patients. Aberrant expression of VE-cadherin has been strongly associated with VM. Even more, human malignant melanoma cells have a constitutively high expression of phospho-VEC (pVEC) at Y658. In this review we focus on non-endothelial VE-cadherin and its post-translational modifications as a prominent factor involved in the development of tubule-like networks by aggressive tumor cells, highlighting the signaling pathways that lead to their pseudo-endothelial and stem-like phenotype and the role of tumor microenvironment. We discuss the importance of the tumor microenvironment in VM acquisition, and describe the therapeutic opportunities derived from the in-depth knowledge of the biology of VE-cadherin and other key components of vascular mimicry vessels.